The Influence of Future Time Perspective on Students’ Entrepreneurial Intentions with Financial Behavior as a Mediating Variable - Komang Pipin Nopia; Keumala Hayati (LPPPIPublishing, 2026)
This study aims to examine the effect of future time perspective on students’ entrepreneurial intentions in Bandar Lampung, with financial behavior acting as a mediating variable. The sample consists of 430 active university students from various higher education institutions in Bandar Lampung, Indonesia, selected using a purposive sampling technique. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings indicate that future time perspective has a positive and significant effect on both financial behavior and students’ entrepreneurial intentions. In addition, financial behavior significantly influences entrepreneurial intention and mediates the relationship between future time perspective and entrepreneurial intention. The proposed model explains 66.3% of the variance in entrepreneurial intention and 22.7% of the variance in financial behavior. These findings provide empirical support for Time Perspective Theory and Behavioral Finance Theory in explaining the formation of entrepreneurial intention. Therefore, students are encouraged to improve time management skills, strengthen entrepreneurial readiness through training and practical experience, and enhance financial literacy, particularly in long-term financial protection such as insurance. Future research is recommended to broaden the research scope, incorporate additional variables, and employ longitudinal designs to obtain more comprehensive insights.